2022
DOI: 10.1111/bjh.18420
|View full text |Cite
|
Sign up to set email alerts
|

A phase 1b/2 clinical study of marstacimab, targeting human tissue factor pathway inhibitor, in haemophilia

Abstract: 300 mg, a single 300-mg loading dose with subsequent 150-mg doses, or 450 mg; with inhibitors: 300 mg). Safety outcomes were treatment-emergent adverse events (TEAEs), injection site reactions, clinical and laboratory parameter changes. Efficacy was assessed by annualised bleeding rates (ABRs). Pharmacokinetics and pharmacodynamics (PD) were also evaluated. Among 26 treated participants [haemophilia A without inhibitor, n = 16 (61.5%); haemophilia A with inhibitor, n = 7 (26.9%); haemophilia B, n = 3 (11.5%)],… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 35 publications
3
12
0
Order By: Relevance
“…Median (range) baseline TGA peak level (a key coagulation-related clinical biomarker) of 9.20 (4.9−45.3) nmol in Chinese participants with severe haemophilia was similar to that seen in non-Asian patients with haemophilia (n = 26). 7 The treatment-related trends in all PD endpoints were similar to those seen in healthy White participants 6 and non-Asian participants with severe haemophilia following administration of a single 300 mg dose of marstacimab. 7 No The small sample size, with one participant with haemophilia B and none with inhibitors, is a potential limitation; however, it was acceptable for the study objectives.…”
supporting
confidence: 59%
See 3 more Smart Citations
“…Median (range) baseline TGA peak level (a key coagulation-related clinical biomarker) of 9.20 (4.9−45.3) nmol in Chinese participants with severe haemophilia was similar to that seen in non-Asian patients with haemophilia (n = 26). 7 The treatment-related trends in all PD endpoints were similar to those seen in healthy White participants 6 and non-Asian participants with severe haemophilia following administration of a single 300 mg dose of marstacimab. 7 No The small sample size, with one participant with haemophilia B and none with inhibitors, is a potential limitation; however, it was acceptable for the study objectives.…”
supporting
confidence: 59%
“…6 C max %CV was also comparable with that seen in non-Asian participants with severe haemophilia. 7 Treatment-related changes were observed for all PD endpoints. The pharmacologic effects of marstacimab lasted more than 7 days on PD markers, and maximum or near-maximum effects occurred most often within the first week.…”
mentioning
confidence: 91%
See 2 more Smart Citations
“…Moreover, other humanized mAbs, such as marstacimab, which specifically binds to the K1 domain of the TFPI, have shown the feasibility and efficacy of targeting TFPI therapies in hemophilia. A phase 1b/2 clinical study demonstrated clinically meaningful reductions in ABRs and treatment-related changes for all pharmacodynamics biomarkers across all marstacimab dose levels in participants with hemophilia ( 120 ). Together, therapeutic advances in hemophilia with targeting TFPI treatments are promising.…”
Section: Novel Strategies For Treating Ha With Inhibitorsmentioning
confidence: 99%